Improve the quality of end-of-life in cancer patients using social representations of nutrition - Llinares-Insa, Lucia Inmaculada; Chisbert-Alapont, Encarna; Benedito-Monleón, María Amparo; González-Navarro, Pilar (Frontiers in Oncology, 2025)
IntroductionThe problems related to nutrition generate great concern in palliative cancer patients and their caregivers. Literature has analyzed the psychological and social problems that nutrition causes. From patient-centered orientation, there are protocols for nutritional care. This psycho-health information is a source of discomfort among patients and families and its absence generates many problems related to nutrition with negative clinical repercussions. Thus, this study aims to analyze the concept of nutrition in advanced cancer patients with palliative care and their caregivers. Furthermore, given that food has an important cultural component as important as it is nutrition, the sociocultural influence on the social representation of nutrition will also be analyzed.MethodsThe study design was qualitative and cross-sectional with a recruitment period lasting 18 months. After the informed consent, a sample of advanced cancer patients (N=57) and their caregivers (N=57) were interviewed individually. The data was analyzed using content analysis and descriptive analysis. The existence of statistical differences between groups (patients and caregivers) was tested by Chi-Square statistics.ResultsResults showed that the perception of nutrition was structured in five categories: health/survival/life (e.g. “healthy”), social relationship (e.g. “intimate relationship”), care (e.g. “care role”), foodstuff (e.g. “vegetables”), and others (“anything”). There were significant differences (p-Value>0.05) in the uses of nutrition between patients and their caregivers and caregivers had higher scores. Then, nutrition was perceived as an act of care and, therefore, patients were expected to strive to eat despite the loss of appetite.DiscussionThis study is one of the first to explore the perception of nutrition emphasize the insufficient consideration of patients’ and caregivers’ needs and perceptions regarding food, as well as the significance of this knowledge in patient-centered care approaches. In this way, it could intervene by first understanding the behavior concerning food and, secondly, redirecting the behavior if it is harmful to the patient or family relationships regarding the health care and well-being of patients with advanced cancer with palliative care.